USING JIGSAW TECHNIQUE IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMK HANDAYANI LUWUK - Desriani Nggolaon; Christina Maitimu (BABASAL English Education Journal, 2021)
This study aims to see the effect of Jigsaw techniques in improving students’ reading comprehension. The population in this research was students of X grade SMK Handayani Luwuk. The research sample involved all students using total sampling technique. The main instrument in collecting research data is test. Data analysis used t-test analysis to compare students’ means score. The calculation result shows that the t-counted value 8.271 is higher than the t-table 1.795. it means that improving students’ reading comprehension by applying Jigsaw technique was effective. The alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that the application of Jigsaw technique is effective in improving students’ reading comprehension.